HUBUNGAN ONLINE FRIENDSHIP QUALITY DENGAN KECEMASAN AKAN MENGHADAPI TUGAS AKHIR STUDI PADA MAHASISWA SEMESTER AKHIR DALAM PANDEMI COVID - 19 - Luna Maheswari Putri Idfar; Flaviana Rinta Ferdian (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2022)
Having friends can reduce the negative effects of stressful experiences such as facing your thesis.Due to the COVID-19 pandemic, it is uncertain whether friendship quality possessed by studentshas a relationship or not with the anxiety experienced by students. According to Foulkes andBlakemore (2021), even for the strongest friendships, socialization via the internet is not the sameas face-to-face interaction. So, the mental health benefits you get are not the same as interactingdirectly. Therefore, this study aimed to see the relationship between online friendship quality andanxiety about the final thesis in final semester students during the COVID-19 pandemic. Thequantitative method used in this research with a correlational research design. One hundred andtwenty-two participants were selected using convenience sampling. Questionnaires wereimplemented as the data collection technique. The data was analyzed using the Pearson Product Moment correlation test. The findings showed that online friendship quality does not have asignificant relationship with anxiety about facing the final thesis in final semester students. Itindicated that the level of one's online friendship quality does not correlate with the level ofanxiety. However, additional test results showed that on the friendship quality variable, thedimensions of conflict and betrayal negatively correlated with all dimensions of the anxiety.